The Well-Dressed Puppet - Lambeth, Cheralyn (Routledge, 2014)
Costumes are an integral part of any performance, adding believability, conveying setting, or establishing the tone, a fact that is no less true when your performer is a puppet! The only book of its kind, The Well-Dressed Puppet will show you how to create costumes and accessories tailored specifically for your puppet that will enhance any performance. Gone are the days of ill-fitting store-bought clothing that restrict the movement and use of your puppet. Author Cheralyn Lambeth walks you through every step of the costume-making process with detailed lists of the necessary materials, equipment, and patterns required to create a costume from scratch. She also shares multiple tips and information on how to modify off-the-rack clothing to fit any puppet. Suitable for both beginners and more advanced costumers, The Well-Dressed Puppet demonstrates basic sewing and construction techniques while still providing advanced projects for customers who have already mastered those skills.